Pemberdayaan Masyarakat Kampung Pelangi Melalui Pelatihan Langkah Cuci Tangan Pakai Sabun pada Ibu Rumah Tangga Di Kelurahan Guntung Paikat Kota Banjarbaru - Fakhriadi, Rudi; Rosadi, Dian; Fadillah, Noor Ahda; Lasari, Hadrianti HD (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2024)
Banjarbaru City is the second city with the highest number of cases after Banjarmasin with 4,411 cases and 123 deaths in 2021. Several health behaviors that can reduce the possibility of being infected with the COVID-19 virus are implementing Clean and Healthy Living Behavior, one of which is by implementing the behavior of washing hands with soap. Therefore, training activities aim to increase the knowledge and behavior of housewives regarding PHBS, especially the practice of washing hands with soap in the household setting. The training method used uses an active participatory method so that participants are free to express opinions and ask questions and practice hand washing steps directly. The target of this activity is 30 housewives in Kampung Pelangi, Guntung Paikat Village, Banjarbaru City. This activity is divided into three stages, namely preparation, implementation and evaluation. The evaluation results showed that there was an increase in the knowledge of the training participants before and after the training. It is hoped that future activities can involve other groups in the household, such as involving the head of the house